Invitations, Incentives, and Conditions : A Randomized Evaluation of Demand-Side Interventions for Health Screenings in Armenia - De Walque, Damien; Chukwuma, Adanna; Ayivi-Guedehoussou, Nono; Koshkakaryan, Marianna (World Bank, Washington, DC, 2020)
The study is a randomized controlled trial that investigates the impact of four demand-side interventions on health screening for diabetes and hypertension among Armenian adults ages 35-68 who had not been tested in the last 12 months. The interventions are personal invitations from a physician (intervention group 1), personal invitations with information about peer screening behavior (intervention group 2), a labeled but unconditional cash transfer in the form of a pharmacy voucher (intervention group 3), and a conditional cash transfer in the form of a pharmacy voucher (intervention group 4). Compared with the control group in which only 3.5 percent of participants went for both screenings during the study period, interventions 1 to 3 led to a significant increase in the screening rate of about 15 percentage points among participants. The highest intervention impact was measured among recipients in intervention group 4, whose uptake of screening on both tests increased by 31.2 percentage points. The levels of cost-effectiveness of intervention groups 1, 2, and 4 are similar while for intervention group 3 it is about twice more expensive per additional person screened.